Role of IgM testing in the diagnosis and post-treatment follow-up of syphilis: a prospective cohort study - Tania Crucitti; Irith De Baetselier; Hilde Smet; Kara K Osbak; Achilleas Tsoumanis; Marjan Van Esbroek; Chris R Kenyon (BMJ Open)
Objectives The diagnosis of repeat syphilis and its follow-up remains challenging. We aimed to investigate if IgM testing may assist in the diagnosis of syphilis reinfection/relapse and its treatment follow-up.Methods This substudy was conducted in the context of a syphilis biomarker discovery study (ClinicalTrials.gov Nr: NCT02059525). Sera were collected from 120 individuals with a new diagnosis of syphilis (72 with repeat infections) and 30 syphilis negative controls during a cohort study investigating syphilis biomarkers conducted at a sexually transmitted infection/HIV clinic in Antwerp, Belgium. Syphilis was diagnosed based on a simultaneous positive treponemal and non-treponemal assay result and/or positive serum PCR targeting polA. Specimens collected at visit of diagnosis, and 3 and 6 months post-treatment were tested by two enzyme immunoassays (EIAs), recomWell (Mikrogen; MI) and Euroimmun (EU), to detect anti-treponemal IgM. Baseline specimens were also tested for anti-treponemal IgM using a line immunoassay (LIA) recomLine (MI). Quantitative kinetic decay curves were constructed from the longitudinal quantitative EIA results.Results An overall sensitivity for the diagnosis of syphilis of 59.8% (95% CI: 50.3%–68.7%), 75.0% (95% CI: 66.1%–82.3%) and 63.3% (95% CI: 54.8%–72.6%) was obtained for the EU, MI EIAs and MI LIA, respectively. When only considering repeat syphilis, the diagnostic sensitivity decreased to 45.7% (95% CI: 33.9%–58.0%), 63.9% (95% CI: 51.7%–74.6%) and 47.2% (95% CI: 35.5%–59.3%), respectively. IgM seroreverted in most cases 6 months after treatment. Post-treatment IgM concentrations decreased almost 30% faster for initial syphilis compared with repeat infection. The IgM EIAs and IgM LIA agreed from fairly to moderately (Cohen’s kappa (κ): 0.36 (EU EIA); κ: 0.53 (MI EIA); κ: 0.40 (MI LIA)) with the diagnosis of syphilis.Conclusions IgM detection was not a sensitive method to diagnose syphilis and was even poorer in the diagnosis of syphilis repeat infections.